Evidence for neuroinflammation in Alzheimer's disease. Issue 5 (September 2016) - Walters, Anna; Phillips, Emma; Zheng, Rui; Biju, Maya; Kuruvilla, Tarun
Abstract : New understanding in neuroscience has established that alongside the amyloid plaques, neurofibrillary tangles and atrophy, the neuroinflammation triggered by the CNS's innate immune response plays a central role in the pathogenesis of Alzheimer's disease (AD). In this review, the authors look at the roles that the cells of the immune response play in the pathogenesis of AD, the influence of genetics, the developing role for neuroimaging to detect inflammation and progress towards potential therapeutic strategies.